Polemik Harun Nasution-H.M. Rasjidi dalam Falsafat dan Teologi - Abdus Syakur (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2015)
This writing is focused on the polemic that occurred between Harun Nasution and H.M. Rasjidi, particularly in the problems of philosophy and theology. In terms of philosophy, it is focused on reason and revelation (al-‘aql wa al-manqūl), whereas of theology is focused on the relevance of Mu‘tazila rational theology. In the view of Harun Nasution, reason can know God (ma‘rifa Allāh), the liability to know God (wujūd ma‘rifa Allāh), to know good and evil (ma‘rifa al-ḥusn wa al-qubḥ) and the liabilities to do good deeds and liabilities to avoid misconduct (wujūb i‘tināq al-ḥasan wa ijtināb al-qabīḥ), while the revelation serves the details of those are known by reason. In the view of H.M. Rasjidi, reason can only know God, while the others can only be known through revelation. Harun Nasution considers that the rational theology of Mu‘tazila is needed as alternative solution to overcome the backwardness of Muslims. H.M. Rasjidi considers that the rational theology of Mu‘tazila is considered dangerous to the power of faith.